The Transformation of Child Character Empathy through Friendship Conflict in the Comic Little Exo-L (Maria Nikolajeva’s Perspective) - Aprilia , Airin Ina; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Global popular culture, specifically K-pop fandom, often serves as a space for identity negotiation and power relations among children in the digital age. This study aims to analyze the character transformation of the protagonist, Rara, in the KKPK comic Little EXO-L by Mutiara Sya’bani, using Maria Nikolajeva’s theoretical perspective. Employing a qualitative descriptive method, the research examines how friendship conflicts function as emotional learning tools to shift egocentric behavior toward ethical awareness. The findings reveal that Rara undergoes a significant emotional trajectory, moving from a phase of authoritarian dominance as a group leader to a moral turning point through guilt and self-reflection. Within Nikolajeva’s framework, this transformation involves the attainment of ethical knowledge, marked by Rara’s decision to abolish hierarchical structures in favor of equality within the friendship. The study concludes that popular children’s comics are not merely entertainment but effective moral laboratories for training empathy and social responsibility. These findings reinforce the position of contemporary children’s literature as a vital medium in shaping the moral identity of the younger generation.